Research methods in health : investigating health and health services - Bowling, Ann. (Buckingham : Open University Press, 1997)
This book is divided into five parts: Investigating health services and health: the scope of research; The philosophy, theory and practice of research; Quantitative research: sampling and research methods; The tools of quantitative research; and Qualitative and combined research methods, and their analysis.
Keywords: Public health; Community health services; Public health -- Research -- Methodology; Community health services -- Research -- Methodology